THE USE OF HERBS AS COMPANION THERAPY IN CASES OF HYPERTENSION: A LITERATURE STUDY - Tati khairina,; Abdullah, Dessy; Yanti Fitri Yasa,; Maryeti Mawarzi, (Nusantara Hasana Journal, 2024)
growing interest in exploring complementary and alternative medicine approaches, including the use of herbal remedies, as adjunct therapies. This literature review examines the current evidence on the efficacy and safety of using herbs as companion therapy in the management of hypertension. The review of the literature indicates that certain herbal supplements, such as garlic, hawthorn, and green tea, have demonstrated the potential to lower blood pressure and may be beneficial when used in conjunction with standard hypertensive medications. However, the available evidence is limited, and further research is needed to establish the long-term safety and efficacy of these herbal treatments. (Lattanzio, R, M. and Weir, R, M., 2020) (Afolayan, A. and Wintola, A, O., 2014) Careful consideration of potential interactions and side effects is crucial when incorporating herbal remedies into the treatment of hypertension. Overall, the findings suggest that the use of herbs as companion therapy in hypertension may offer a promising complementary approach, but healthcare providers and patients should exercise caution and closely monitor the effects to ensure the optimal management of this chronic condition.